The effectiveness of cooperation with research institutes (observatories) in the teaching of astrophysics - Hotamov, Jaxongir; Bobonazarov, Dilshod (Физико-технологического образование, 2021)
This article demonstrates the effectiveness of teaching using virtual laboratories in the process of laboratory work on the subject of "Astrophysics" in pedagogical universities, as well as the establishment of close ties with research institutes.